Analisis Spesialisasi dan Konsentrasi Spasial Industri Manufaktur di Provinsi Jawa Timur - Syamsul Maarif; Duwi Yunitasari; Regina Niken Wilantari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
Industrial cluster is a phenomenon that is often found in the manufacturing industry so it is interesting to be analyzed and researched. The purpose of this study is to determine in what sub-sectors the manufacturing industry in East Java Province is specialized and where is the spatial concentration of the manufacturing industry in East Java Province. This study uses analysis tools, Krugman Specialization Index, Location Quotient (LQ), Herfindahl Index and Elisson-Glaeser Index. Based on the results of the analysis of the specialization of the regional krugman index that has specialization, namely, Tuban Regency and the City of Kediri. Based on the results of the Location Quotient (LQ) analysis, the manufacturing industry of East Java Province specializes in 11 subsectors. Based on the analysis of the Herfindahl Index, the manufacturing industry in East Java Province is spatially concentrated in several districts or cities, namely, Bojonegoro Regency, Gresik Regency, Kediri City, Surabaya City, Pasuruan Regency and Sidoarjo Regency and based on the Elisson Glaeser index the spatial concentration is supported by the role of natural advantage and knowledge spillover.